Determinants of Sharia Bank Customer Loyalty in Abu Zahrah's Maqashid Syariah Approach - Mulyani, Sri; Diana, Ilfi Nur; Yuliana, Indah (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
This study arose from the need to understand customer loyalty in Islamic banking through Abu Zahrah's maqashid sharia framework. The objective was to examine the influence of Islamic Branding Experience, customer satisfaction, and customer retention on customer loyalty, and to analyze the mediating role of Customer Citizenship Behavior. The method used was a quantitative explanatory study with 355 Islamic bank customer respondents and data analysis using Structural Equation Modeling – Partial Least Squares (SEM‑PLS). The results showed that Islamic Branding Experience, customer satisfaction, and customer retention significantly influence customer loyalty, both directly and indirectly through Customer Citizenship Behavior. These findings confirm that Customer Citizenship Behavior plays an important mediating variable between IBE, customer satisfaction, retention, and loyalty in the context of Abu Zahrah's maqashid sharia. In conclusion, this study successfully developed and validated customer loyalty dimensions based on maqashid sharia, providing theoretical contributions and practical implications for developing marketing strategies and improving customer relationships in Islamic financial institutions.